A study of variations in formation of superficial palmar arch in Nepalese cadavers - Baral, Prakash; Shrestha, Rami; Sapkota, Subash; Koju, Supana; Chaudhary, Binod (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: The superficial palmar arch (SPA) is the main source of arterial supply to the palm. It is an arterial arcade formed mainly by the ulnar artery and is completed by the superficial palmar branch of the radial artery. The study was conducted with objective to study the variations in formation of superficial palmar arch in Nepalese cadaveric hands. Methodology: Two horizontal incisions were made, one at the wrist joint and another incision along the root of fingers. A vertical incision was made from the middle of the wrist to the 3rd metacarpo-phalangeal joint. The skin of the palm and the palmar aponeurosis was reflected. The surrounding adipose tissue was removed to view the superficial palmar arch and its branches. Result: In present study, out of 50 specimens of hands, 64% of superficial palmar arch was formed as normal pattern and in 36% cases it was formed by ulnar artery alone. Normal SPA pattern was seen 63% in male and 66.7% in female i.e. higher percentage in female than in male but it was statistically insignificant (P<0.05). SPA-ulnar artery alone pattern was seen 37% in male and 33.3% in female i.e. higher percentage in male than in female, however it was also statistically insignificant (P<0.05). Conclusion: Normal pattern of SPA observed in Sixty-four percent of Nepalese hands and in thirty-six percent cases it was formed by ulnar artery alone. There was no statistically significant difference in SPA pattern distribution between Nepalese male and female.